2020
DOI: 10.1002/marc.202000448
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanocrystal (CNC)–Latex Nanocomposites: Effect of CNC Hydrophilicity and Charge on Rheological, Mechanical, and Adhesive Properties

Abstract: Cellulose nanocrystals (CNCs), a sustainable nanomaterial, are in situ incorporated into emulsion‐based pressure‐sensitive adhesives (PSAs). Commercially available CNCs with different surface hydrophilicity and surface charge (CNC101 and CNC103 from CelluForce) are used to explore their role in PSA property modification. Viscosity measurements and atomic force microscopy reveal differences in degree of association between the CNCs and the latex particles depending on the surface properties of the CNCs. The mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
65
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 26 publications
(71 citation statements)
references
References 75 publications
(72 reference statements)
6
65
0
Order By: Relevance
“…Compared to the use of hydrophobic CNCs in MEP, hydrophilic and partially hydrophobic CNCs improved tack, peel strength, and shear strength (Figure 5). [ 39 ] Hydrophilic CNCs considerably increased the shear up to 0.75 wt% loading (Figure 5C), which was attributed to the formation of long CNC aggregates in the final film. Further increases in hydrophilic CNC loadings resulted in highly elastic polymers, which led to a reduction in all three adhesive properties and making these films inappropriate for use as PSAs (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to the use of hydrophobic CNCs in MEP, hydrophilic and partially hydrophobic CNCs improved tack, peel strength, and shear strength (Figure 5). [ 39 ] Hydrophilic CNCs considerably increased the shear up to 0.75 wt% loading (Figure 5C), which was attributed to the formation of long CNC aggregates in the final film. Further increases in hydrophilic CNC loadings resulted in highly elastic polymers, which led to a reduction in all three adhesive properties and making these films inappropriate for use as PSAs (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…The increase in viscosity was much lower than previously found with the use of water‐dispersible CNCs in CEP (up to 350 mPa s). [ 39 ] Figure 2 shows the evolution of monomer conversion, particle size, N p and N p / N d for the runs shown in Table 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…While unmodified CNCs are slightly amphiphilic [28] and can stabilize monomer/water interfaces [29,30], they have not been demonstrated on their own as the sole stabilizer in latex-based PSA synthesis. However, recent work has shown that CNCs surface modified to be sufficiently amphiphilic to be surface active resulted in even better PSA performance due to their improved affinity with the monomer/polymer phase [31]. The effect of this modification is inferred to be twofold, the higher affinity between the CNCs and the polymer (i) improved CNC dispersion throughout the latex, ensuring no aggregation upon drying and a homogeneous PSA film [31] and (ii) enabled the CNCs to act as entanglement points for the polymer chains, improving the cohesive strength of the PSA [32].…”
Section: Introductionmentioning
confidence: 99%